Shared Massage Chair Application in the Context of IoT: Take "Lemobar" as an Example. (September 2020) - Jiang, Qingquan; Lin, Qiaozhen; Zhang, Rui; Huang, Honggang
Abstract: The increase in productivity brought about by every technological change in history will also profoundly affect and change people's lifestyles and habits. The increasing maturity and wide application of the Internet of Things technology has brought unlimited possibilities for business. The further development of artificial intelligence will make big data integrated through the Internet of Things and create greater value. The "sharing economy" has deeply affected people's lives in recent years and been widely reported and triggered by many scholars' research. This paper explores the shared massage chair that is rarely studied from a technical point of view, compared to the popular shared bicycle, shared power bank, and takes Lemobar as an example, which is so far the benchmarking in the shared massage industry. This paper innitially concludes the development process of shared massage that is changing with technological progress, and furthermore analyzes the shared massage application including software & hardware support, operation management, system integration and different kind of scenarios combination. The application of Lemobar is a remarkable case of human and machine interaction in the context of Internet of Things and big data.